Comparative study between teachers and students on acceptance and use of technologies for educational purposes in the Chilean context - María Luisa Arancibia Muñoz; Julio Cabero Almenara; Ismael Valdivia Zamorano (Universidad de Guadalajara, 2019)
Nowadays, it is expected that technologies be integrated in teaching and learning processes. To achieve this goal, it is also necessary to recognize a series ofpersonal, institutional and formation factors that influences in the integration of these technologies. This study explores chilean university teachers and students perceptions about technology valuation, uses and acceptation for educational matters. Main results shows a high level of access to technology, especially the computer and smartphones, this last one highly valuated for academic achievement. Teachers had higher expectations for the use of ICT in teaching, using more diversity of them with multiple purposes, unlike students that presented a reduction of use, although with a high valuation of technologies. It is highlighted the smartphone valuation as a means of ubiquitous, mobile and contextualized learning. Also, a positive correlation is showed between perception of facility and utility of use of the Moodle platform, and a positive perception about b-learning models. Finally, the implications of the study for the processes of integration of ICTs in higher education contexts are presented and future lines of research are enunciated.